MICROBIAL TRANSFORMATION OF CHOLESTEROL BY MYCOBACTERIUM SMEGMATIS (Journal of Sciences, Islamic Republic of Iran)
Mycobacterium smegmatis PTCC 1307 (CIP 73.26) was used as a microbial agent to produce androsta-1,4-diene-3,17-dione (ADD) and androst-4-ene-3,17-dione, two useful precursors in the synthesis of steroid drugs. The side chain of cholesterol, as the substrate, was selectively cleaved in the presence of five enzyme inhibitors. An intermediate structure with intact side chain, cholest-4-ene-3-one, was also detected and purified.